The general control nonderepressible‐2 kinase mediates stress response and longevity induced by target of rapamycin inactivation in Caenorhabditis elegans. Issue 5 (28th June 2013) - Rousakis, Aris; Vlassis, Arsenios; Vlanti, Anna; Patera, Stefania; Thireos, George; Syntichaki, Popi
Summary: The general control nonderepressible 2 (GCN2) kinase is a nutrient‐sensing pathway that responds to amino acids deficiency and induces a genetic program to effectively maintain cellular homeostasis. Here we established the conserved role of Caenorhabditis elegans GCN‐2 under amino acid limitation as a translation initiation factor 2 (eIF2) kinase. Using a combination of genetic and molecular approaches, we showed that GCN‐2 kinase activity plays a central role in survival under nutrient stress and mediates lifespan extension conferred by dietary restriction (DR) or inhibition of the major nutrient‐sensing pathway, the target of rapamycin (TOR). We also demonstrated that the GCN‐2 and TOR signaling pathways converge on the PHA‐4/FoxA transcription factor and its downstream target genes to ensure survival of the whole organism under a multitude of stress conditions, such as nutrient scarcity or environmental stresses. This is one step forward in the understanding of evolutionary conserved mechanisms that confer longevity and healthspan.